NOMO-1 cells expressing an NF-κB luciferase reporter gene facilitate a simple, rapid monocyte activation test that can detect a wide range of pyrogens. - Tomohisa Nanao; Yuki Marutani; Katsuko Sato; Tomohiro Mori; Takeshi Kitagawa; Teruaki Oku; Takahiro Nishibu (PLoS ONE)
Pyrogens, which include endotoxin and non-endotoxin pyrogens (NEPs), act on immune cells in the bloodstream, causing various effects such as fever and endotoxic shock. The limulus amebocyte lysate test, a commonly used endotoxin test in the manufacturing of pharmaceuticals and medical devices, can detect endotoxin but not NEPs. The monocyte activation test (MAT), which uses monocytes, is a testing method included in the European Pharmacopoeia (EP 11.5; 07/2024:20630) that can detect NEPs. The MAT detects the cellular response following activation of Toll-like receptors (TLRs) by pyrogens; released cytokines, such as IL-6, are often the targets of detection. This cytokine release is regulated by the transcription factor NF-κB. In this study, we investigated whether it is possible to detect pyrogens with an NF-κB reporter gene-expressing cell line, using the NOMO-1 cell line as a model monocyte-like line. This study demonstrates that the reporter gene-expressing cells can detect 0.0125 EU/mL lipopolysaccharide (LPS) after 3 hours of incubation, and a stable calibration curve for LPS quantification can be created. Moreover, these cells can detect agonists for TLR1-9 in a concentration-dependent manner. Pharmaceuticals, including blood products and antibody drugs, were used in LPS recovery tests to confirm that they do not interfere with LPS detection. This study demonstrates that NF-κB reporter cells facilitate a simpler, more concise MAT, eliminating the complexity associated with enzyme-linked immunosorbent assays. Moreover, using the NOMO-1 cell line allows for the detection of a wider range of NEPs compared with using existing reporter gene-expressing cell lines.